CICLO DE VIDA Y DESCRIPCIÓN DE ESTADOS INMADUROS DE EPICLINES GAYI CHEVROLAT, 1838 (COLEOPTERA: CLERIDAE: CLERINAE) (Acta Entomológica Chilena, 2022)
The life cycle oí E piclines g a yi under laboratory conditions is studied. The whole cycle is achieved in one year. Oviposition occurs in early spring. Six to eight larval instars are recognized. Mature larvae, o f 6o, 7o or 8o instar, overwinter and pupate in the following spring. Egg, mature larva and pupa are described.
Keywords: E piclines gayi, Cleridae, life cycle, immature stages